Hepatitis B and breastfeeding in Hangzhou, Zhejiang Province, People's Republic of China. - Qiu, L.; Binns, Colin; Zhao, Yun; Zhang, K.; Xie, X. (Mary Ann Liebert, Inc. Publishers, 2010)
Objective: This study examined infant feeding methods in hepatitis B-positive mothers in Zhejiang Province, People's Republic of China. Methods: A cohort study was undertaken in Hangzhou in Zhejiang Province. A sample of 638 mothers was recruited at birth from the city of Hangzhou and was followed up until their infants were 6 months of age. Results: Chronic hepatitis B is a continuing public health issue in pregnant women. Breastfeeding is the foundation of infant nutrition, sets the scene for lifetime health, and is important for all mothers. In the Hangzho cohort of 638 mothers, 38 were identified as hepatitis B positive, a rate of 6.0%. All of the infants of the hepatitis B-positive mothers were fed on formula immediately after birth while their breastmilk was tested for virus transmission and their infants were vaccinated. At 1 month of age 61.8% of the hepatitis B-positive mothers were breastfeeding compared to 92% of the remainder of the cohort. The rates at 3 months were 60.6% and 89% and at 6 months were 45.5% and 64%, respectively. The hazard ratio for hepatitis B-positive mothers discontinuing breastfeeding before 6 months was 3.69 (95% confidence interval, 2.28, 5.98). Conclusions: The World Health Organization recommends that all mothers who are hepatitis B positive breastfeed their infants and that their infants be immunized at birth. In this study breastfeeding rates of hepatitis B-positive mothers were substantially less than those of the other mothers.